2022
DOI: 10.3390/antiox11050982
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the SGLT2 Inhibition on Cardiac Remodeling in Streptozotocin-Induced Diabetic Rats, a Model of Type 1 Diabetes Mellitus

Abstract: Clinical trials have shown that sodium glucose co-transporter 2 (SGLT2) inhibitors improve clinical outcomes in diabetes mellitus (DM) patients. As most studies were performed in Type 2 DM, the cardiovascular effects of SGLT2 inhibition still require clarification in Type 1 DM. We analyzed the effects of SGLT2 inhibitor dapagliflozin on cardiac remodeling in rats with streptozotocin-induced diabetes, an experimental model of Type 1 DM. Methods: Male Wistar rats were assigned into four groups: control (C, n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Dapagliflozin reduced blood glucose and body weight loss. This long-term result is in accordance with a previous study in which dapagliflozin was administered for 8 weeks in Type 1 DM rats [ 22 ]. Although the reduced glycemia and better cell environment may be crucial for body mass preservation, the mechanisms involved in this effect are not clear, especially considering that a major action of SGLT2 inhibitors is to decrease renal glucose reabsorption.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Dapagliflozin reduced blood glucose and body weight loss. This long-term result is in accordance with a previous study in which dapagliflozin was administered for 8 weeks in Type 1 DM rats [ 22 ]. Although the reduced glycemia and better cell environment may be crucial for body mass preservation, the mechanisms involved in this effect are not clear, especially considering that a major action of SGLT2 inhibitors is to decrease renal glucose reabsorption.…”
Section: Discussionsupporting
confidence: 92%
“…We have previously observed that short-term administration of SGLT2 inhibitor dapagliflozin is safe, and reduces glycemia, cardiac remodeling and oxidative stress in rats with Type 1 DM [ 22 ]. Several mechanisms have been proposed to explain the effects of SGLT2 inhibition in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…SGLT2i inhibitors can reduce EAT abnormalities, reduce water and sodium retention, and reduce the risk of HFpEF combined with atrial fibrillation. (iv) Anti-myocardial fibrosis and inhibition of ventricular remodeling: SGLT2 inhibitors can reduce the release of inflammatory factors, thereby reducing myocardial fibrosis [ 41 , 42 ]. SGLT2 inhibitors can also reverse LV remodeling by reducing Na + and NHE-1 receptor activity in cardiomyocytes to slow myocardial fibrosis and cardiac hypertrophy [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same drug was also tested in Black and Tan Brachyury (BTBR) mice by Moy et al, which are bred for insulin resistance [ 32 ], and was found to limit the fibrotic impact and pathological remodeling of the left ventricle implicating SGLT2i as the potential for improving heart function [ 33 ]. Among a type I diabetic rat model induced by streptozotocin, dapagliflozin had a lower type I-to-type III collagen ratio and the most common type of collage found in the myocardium [ 34 ] with lesser reactive oxygen species concentrations in tissues [ 35 ]. Findings correlate with improved myocardial tissue health and thereby can be associated with a likely potential benefit in reducing harmful cardiac changes with SGLT2i use.…”
Section: Reviewmentioning
confidence: 99%